2018
DOI: 10.1177/0963689718779766
|View full text |Cite
|
Sign up to set email alerts
|

Improved Healing after the Co-Transplantation of HO-1 and BDNF Overexpressed Mesenchymal Stem Cells in the Subacute Spinal Cord Injury of Dogs

Abstract: Abundant expression of proinflammatory cytokines after a spinal cord injury (SCI) creates an inhibitory microenvironment for neuroregeneration. The mesenchymal stem cells help to mitigate the inflammation and improve neural growth and survival. For this purpose, we potentiated the function of adipose-derived mesenchymal stem cells (Ad-MSCs) by transfecting them with brain-derived neurotrophic factor (BDNF) and heme oxygenase-1 (HO-1), through a lentivirus, to produce BDNF overexpressed Ad-MSCs (BDNF-MSCs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 50 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…In this study, we found that transplantation of NRG1-BMSCs notably reduced neuronal chromatolysis after SCI. Concomitantly, our data also showed that an overt reduction or absence of GAP43 protein expression in SCI rats, which was in agreement with the observations in a previous study [46]. Interestingly, the sharp reduction of GAP43 caused by SCI was distinctly eliminated with NRG1-BMSCs administration.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that transplantation of NRG1-BMSCs notably reduced neuronal chromatolysis after SCI. Concomitantly, our data also showed that an overt reduction or absence of GAP43 protein expression in SCI rats, which was in agreement with the observations in a previous study [46]. Interestingly, the sharp reduction of GAP43 caused by SCI was distinctly eliminated with NRG1-BMSCs administration.…”
Section: Discussionsupporting
confidence: 93%
“…The huMSCs have been con rmed to differentiate into CNS cell lineages in a rat SCI model [28,30,31] . Some authors investigated BM-MSC transplantation in dogs [32,33] . Among them, Ryu et al [32] recorded improved neurological outcomes in MSC groups after acute transplantation (one week after trauma), since all dogs exhibited purposeful hind limb motion.…”
Section: Discussionmentioning
confidence: 99%
“…These cells are found within the adult bone marrow, where they contribute to hematopoiesis and bone regeneration. BM-MSCs can not only be obtained from humans, rodents, or primates, but also from several animal species such as sheep, dogs, cats, and bovines (Figure 3) [88,92,93,94,95,96,97,98].…”
Section: Mscsmentioning
confidence: 99%